2020
DOI: 10.3233/jad-190439
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events and Racial Disparities in Cognition Among Middle-Aged and Older Adults

Abstract: Background: It is well-documented that African Americans have elevated risk for cognitive impairment and dementia in late life, but reasons for the racial disparities remain unknown. Stress processes have been linked to premature age-related morbidity, including Alzheimer's and related dementias (ADRD), and plausibly contribute to social disparities in cognitive aging. Objective: We examined the relationship between stressful life events and cognitive decline among African American and White participants enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 62 publications
1
50
0
Order By: Relevance
“…Various social and demographic factors that have been studied for health disparities in Alzheimer’s dementia include educational attainment ( Weuve et al, 2018 ), bilingualism ( Lamar et al, 2019 ), neighborhood greenness ( Brown et al, 2018 ), and stressful life events ( Zuelsdorff et al, 2020 ). Similar social and economic aspects may also affect the diet quality by race, including education and income ( Raffensperger et al, 2010 ), health literacy ( Kuczmarski et al, 2016 ), food prices and diet costs ( Townsend et al, 2009 ) and neighborhood grocery store availability ( Powell et al, 2007 ; Bower et al, 2014 ).…”
Section: Racial/ethnic Differences In Healthmentioning
confidence: 99%
“…Various social and demographic factors that have been studied for health disparities in Alzheimer’s dementia include educational attainment ( Weuve et al, 2018 ), bilingualism ( Lamar et al, 2019 ), neighborhood greenness ( Brown et al, 2018 ), and stressful life events ( Zuelsdorff et al, 2020 ). Similar social and economic aspects may also affect the diet quality by race, including education and income ( Raffensperger et al, 2010 ), health literacy ( Kuczmarski et al, 2016 ), food prices and diet costs ( Townsend et al, 2009 ) and neighborhood grocery store availability ( Powell et al, 2007 ; Bower et al, 2014 ).…”
Section: Racial/ethnic Differences In Healthmentioning
confidence: 99%
“…These comorbidities and risk factors include but are not limited to: cardio- 7 and cerebrovascular disease; 8 metabolic disorders of lipid and glucose metabolism including diabetes and obesity; 9-11 immune dysfunction; 12,13 and behavioral risk factors for many dementia comorbidities such as smoking, dietary behavior, physical inactivity, and possibly stress. [14][15][16] The racial/ethnic and socioeconomic health disparities in VCID have been described yet are not well understood, and often are consistent with health disparity patterns in other age-related comorbidities. We expect that promoting a fuller and deeper understanding of the mechanisms of VCID at molecular, cellular, and systems levels across the wide spectrum of pathologies, chronic systemic comorbidities, and other risk factors may lead to potential prevention and treatment strategies to decrease the burden of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic systemic comorbidities and risk factors are also associated with deleterious cognitive outcomes. These comorbidities and risk factors include but are not limited to: cardio‐ 7 and cerebrovascular disease; 8 metabolic disorders of lipid and glucose metabolism including diabetes and obesity; 9‐11 immune dysfunction; 12,13 and behavioral risk factors for many dementia comorbidities such as smoking, dietary behavior, physical inactivity, and possibly stress 14‐16 . The racial/ethnic and socioeconomic health disparities in VCID have been described yet are not well understood, and often are consistent with health disparity patterns in other age‐related comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, people with depression have a higher risk for Alzheimer’s. According to a research study done at the University of Wisconsin, African Americans who reported more stressful events in their lives, such as living in a disadvantaged neighborhood, bankruptcy, alcoholism, and educational complications, were linked with low cognitive function ( Zuelsdorff et al, 2020 ). Another study done at UCSF found a higher rate of dementia in African American participants living in states with high infant mortality.…”
Section: Introductionmentioning
confidence: 99%